O ambiente institucional e a dinâmica organizacional: as políticas de diversidade em uma Universidade Federal - Pereira, Willian Cássio Damasceno (2020)
This research investigates the relationship between transformations in the institutional environment and the processes of reconfiguration and differentiation of the internal structures of organizations. This is done by articulating sociological institutionalism in organizational analysis and the approach to organizational processes developed by Karl Weick. The investigation is associated with the context of current national affirmative action policies for diversity and inclusion and their impacts at the Federal University of São Carlos (UFSCar). Actions seeking to promote diversity and inclusion in higher education gained strength internationally since the 1960s, being associated with the restructuring of the ideological bases of capitalism. In Brazil, these trends culminated in the approval of Federal Law Number 12.711/12, which establishes the Vacancy Reserve Law and also Law 13.409/16, which determines the reservation of vacancies for people with disabilities in technical and higher education courses in the federal network education. It seeks to understand how this transformation in the institutions boosted the performance of certain internal groups of the institution and how these groups led the creation of new organizational areas, negotiating their relations and spaces with the existing structures. As a method, documentary analyzes were used, as well as data obtained through semi-structured interviews with organizational actors who are or were part of UFSCar, in sectors linked to issues of diversity and inclusion. The relationship between environmental issues of diversity and the change in the university's internal structure resulted in the adoption of a new order, based on the equal right of access and the construction of an area that became evident and culminated with a specialized secretary: SAADE.